2015
DOI: 10.1016/j.biopsycho.2014.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Electromyographically assessed empathic concern and empathic happiness predict increased prosocial behavior in adults

Abstract: The relation between empathy subtypes and prosocial behavior was investigated in a sample of healthy adults. "Empathic concern" and "empathic happiness," defined as negative and positive vicarious emotion (respectively) combined with an other-oriented feeling of “goodwill” (i.e. a thought to do good to others/see others happy), were elicited in 68 adult participants who watched video clips extracted from the television show Extreme Makeover: Home Edition. Prosocial behavior was quantified via performance on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
35
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 57 publications
(65 reference statements)
2
35
1
1
Order By: Relevance
“…Gratitude and forgiveness not only relate to prosocial behavior but also to individuals' happiness (Strohminger and Nichols, 2014;Phillips et al, 2017;Han et al, 2019). In the past, some scholars (Meier and Stutzer, 2008;Weinstein and Ryan, 2010;Rudd et al, 2014;Light et al, 2015;Sulemana, 2016;Erreygers et al, 2019) have already reported an association between happiness and prosocial behavior. Overall, results from those studies confirm the usefulness not only of the social cognitive theories but also the adoption of a positive psychology approach (Seligman, 2002;Peterson and Seligman, 2004) in understanding the factors that lead individuals to adopt prosocial behaviors.…”
Section: Virtues (Gratitude and Forgiveness)mentioning
confidence: 99%
See 1 more Smart Citation
“…Gratitude and forgiveness not only relate to prosocial behavior but also to individuals' happiness (Strohminger and Nichols, 2014;Phillips et al, 2017;Han et al, 2019). In the past, some scholars (Meier and Stutzer, 2008;Weinstein and Ryan, 2010;Rudd et al, 2014;Light et al, 2015;Sulemana, 2016;Erreygers et al, 2019) have already reported an association between happiness and prosocial behavior. Overall, results from those studies confirm the usefulness not only of the social cognitive theories but also the adoption of a positive psychology approach (Seligman, 2002;Peterson and Seligman, 2004) in understanding the factors that lead individuals to adopt prosocial behaviors.…”
Section: Virtues (Gratitude and Forgiveness)mentioning
confidence: 99%
“…Moreover, happiness plays an important role in adolescent positive outcomes (Park and Peterson, 2006;Proctor et al, 2010;Mongrain et al, 2011;Rana et al, 2014). In fact, evidence suggests that those who are happier are more likely to exhibit prosocial behavior in the future (Thoits and Hewitt, 2001;Walker, 2007;Meier and Stutzer, 2008;Rudd et al, 2014;Light et al, 2015;Sulemana, 2016). However, no studies were found reporting on the relationship between happiness and prosocial bystander behavior in bullying.…”
Section: Happinessmentioning
confidence: 99%
“…One may note that the lack of correlation between empathy for pain and prosociality in our study is at odds from the above study. However, this difference could be explained by the possibility that real‐world donations are a more sensitive measure for prosocialness, as suggested by studies in which prosociality is measured by real‐world donations [Light et al, ] or actual helping behaviours [Waytz et al, ].…”
Section: Discussionmentioning
confidence: 99%
“…Generally speaking, PE refers to conditions in which imagining, recalling, observing, or learning of others' positive outcomes can trigger positive states in the empathizer. Operationally, PE has been described referring to the following three distinct empathic states: (i) empathic cheerfulness, which is the display of positive emotion to a suffering person in order to cheer that person up [Light et al, ]; (ii) empathic happiness, a joyful response to positive events that involve others [Batson et al, ]; and (iii) goodwill, the desire to see others in a happy state [Light et al, ], which may represent an innate attitude in promoting prosocial behaviours. While scarce, previous studies indicate that personal and vicarious rewards may be represented in both distinct and overlapping neural networks [Knutson et al, ; Krishnan et al, ; Liu et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Zygomaticus and corrugator responses appear to be independent, as they can be separately activated [85, 86], likely have unrelated time courses [87, 88], and can be concurrently assessed [e.g., 89, 90, 91]. Mixed smiles, comprising of activation of both zygomaticus and corrugator, have been documented over the averaged time course of brief film clips [29, 30], with second-by-second simultaneous occurrence [92, 93, 94, 11] and coinciding onset [95].…”
Section: Objective Measures For Assessing Mixed Emotionsmentioning
confidence: 99%